The Strategy of Islamic Religious Education Teachers in Instilling Disciplined Character in Students at SMA N 1 IV Koto, Agam Regency - Dillah Suci Ananda; Junaidi Junaidi; Darul Ilmi; Deswalantri Deswalantri (The Future of Education Journal, 2023)
Character education is education that helps and facilitates students to develop into perfect human beings and human beings. This study aims to determine the strategies and obstacles faced by Islamic religious education teachers in building the disciplinary character of students at SMA N 1 IV Koto. This type of research is the author's. used is field research (field research) which aims to describe, an accurate picture of the facts of the phenomenon that is being stalled. The key informants in this study were students at SMA N 1 IV Koto and PAI teachers, school principals, and colleagues as supporting informants. The results of research conducted at SMA N 1 IV Koto show that the strategies of PAI teachers in shaping the disciplinary character of students at SMA N 1 IV Koto with direct education include: example, advice, training, competition, and habituation. While education indirectly, including: prohibition, correction, supervision and punishment. The obstacles found in the formation of student discipline character are the lack of student interest, lack of understanding of student and family knowledge.